2012
DOI: 10.1152/ajprenal.00206.2011
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal localization of the plasma membrane ATP channel pannexin1

Abstract: In the renal tubules, ATP released from epithelial cells stimulates purinergic receptors, regulating salt and water reabsorption. However, the mechanisms by which ATP is released into the tubular lumen are multifaceted. Pannexin1 (Panx1) is a newly identified. ubiquitously expressed protein that forms connexin-like channels in the plasma membrane, which have been demonstrated to function as a mechanosensitive ATP conduit. Here, we report on the localization of Panx1 in the mouse kidney. Using immunofluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 40 publications
(71 reference statements)
4
57
0
Order By: Relevance
“…For confocal immunofluorescence microscopy, kidney sections (5-μm thickness) were shipped to the laboratory of JP-P at the University of Southern California. These sections were processed by methods described previously [10,16,28]. Briefly, deparaffinized and rehydrated sections were heated for 2 × 10 min in a microwave with medium heat in PBS and allowed to cool for 40 min to retrieve antigen.…”
Section: Morphological Examination and Confocal Immunofluorescencementioning
confidence: 99%
“…For confocal immunofluorescence microscopy, kidney sections (5-μm thickness) were shipped to the laboratory of JP-P at the University of Southern California. These sections were processed by methods described previously [10,16,28]. Briefly, deparaffinized and rehydrated sections were heated for 2 × 10 min in a microwave with medium heat in PBS and allowed to cool for 40 min to retrieve antigen.…”
Section: Morphological Examination and Confocal Immunofluorescencementioning
confidence: 99%
“…More recently, pannexin 1 channels (Panx1), expressed at the apical membrane of ICs, has also been proposed to regulate ATP release as Panx1-deficient mice excrete less ATP than their wild-type littermates (15,46). Thus, ATP released via Cx30 and/or Panx1 is theoretically available for autocrine and paracrine signaling to ICs and PCs, respectively.…”
Section: Figurementioning
confidence: 99%
“…Although most studies have focused on the contribution of vascular Cx proteins to renal hemodynamics, accumulating evidence suggests an essential physiological role for these proteins in tubular epithelial function. Regarding the Panx family, our knowledge is still limited, as today there are only two studies reporting their expression throughout different renal compartments [17,18]. It should be noted though that Panx localization in some experiments was performed in paraffin-embedded tissues [17].…”
Section: Connexin and Pannexin Distribution In The Kidneymentioning
confidence: 99%
“…Indeed, urinary ATP levels were reduced by 30 % in Panx1 KO mice compared to wild-type mice. Since Panx1 was located at the apical membrane of various tubular segments, the authors suggested that Panx1-based channels may regulate ATP release and further participate in the control of renal epithelial fluid, electrolyte transport and vascular functions via purinergic signaling [18].…”
Section: Gap Junctions and Tubular Functionmentioning
confidence: 99%
See 1 more Smart Citation